Seroma Formation in Ventral Wall Hernia After Mesh Repair: Impact of Tranexamic Acid in Its Prevention - Aftab, Aliza Latif; Anwar, Muhammad Imran (Biological and Clinical Sciences Research Journal, 2025)
Seroma formation is a common postoperative complication following mesh repair for ventral wall hernias, contributing to patient morbidity and prolonged hospital stays. Tranexamic acid (TXA), known for its antifibrinolytic action, is believed to limit postoperative fluid collection by reducing intraoperative bleeding. Its use may contribute to improved recovery. This study aimed to assess the effectiveness of TXA in reducing seroma incidence and improving surgical outcomes in a Pakistani population. Objective: To evaluate the impact of tranexamic acid on postoperative seroma formation and other surgical outcomes in patients undergoing ventral hernia mesh repair. Methods: This randomized controlled trial was conducted at the Department of Surgery, Shaikh Zayed Hospital, Lahore, from December 2024 to May 2025. A total of 120 patients undergoing elective open mesh repair for primary or incisional ventral hernia were randomized into two groups: Group A received intravenous TXA (1 g in 100 ml NS) at the time of skin incision followed by oral TXA 1g BID till third post operative day whilst Group B received a placebo (100 ml NS). Standard onlay mesh repair and postoperative protocols were followed. The primary outcome was the incidence of seroma; secondary outcomes included drain output, pain scores, haemoglobin drop, and length of hospital stay. Data were analysed using SPSS 20.0, with p<0.05 considered statistically significant. Results: The incidence of seroma was significantly lower in the TXA group compared to the control group (6.7% vs.21.7%, respectively, P=0.023). TX group also showed reduced considerably drain output (95.3±19.4ml vs.144.2±24.6ml, p <0.001), lower pain scores (3.6±0.9 vs. 4.6±1.1, p <0.001), smaller haemoglobin drop (0.8±0.3g/dL vs.1.4±0.4g/dL p<0.001), and shorter hospital stay (1.7±0.4 days vs.2.3±0.5 days, p<0.001). Higher BMI, diabetes, and larger defect size were significantly associated with increased risk of seroma. Multivariate analysis confirmed TXA as a protective factor (OR 0.25, p=0.022). Conclusion: Tranexamic acid significantly reduces the risk of postoperative seroma and improves key recovery parameters in patients undergoing ventral hernia repair. Its routine use may enhance surgical outcomes, especially in resource-constrained healthcare settings, such as those in Pakistan.